Synthesis, characterizations and anti-corrosion screening of sadimine and brosadimine / Nur Anis Atirah Zulkiflee and Siti Noriah Mohd Shotor - Zulkiflee, Nur Anis Atirah; Mohd Shotor, Siti Noriah (Universiti Teknologi MARA, Negeri Sembilan, 2020)
This paper deals with a review of the inhibition activity of a Schiff bases on the deterioration of mild steel in hydrochloric acid media. Two Schiff base ligands namely N,N'- Bis(salicylidene)-ethylenediamine (Sadimine) and N,N'-Bis(bromosalicylidene)- ethylenediamine (Brosadimine) were synthesized from the condensation reactions of salicylaldehyde or 5-bromosalicylaldehyde with ethylenediamine respectively and evaluated as corrosion inhibitor for mild steel in 1 M HCl solution using weight loss method. The use of inhibitors is one of the most practical methods for protection of mild steel against corrosion in acidic media. Schiff bases are widely being employed in such applications. This paper highlights the influence of structure-inhibition activity relationship of Schiff base compounds on their performance as corrosion inhibitors of mild steel in acid media. Sadimine and Brosadimine show appreciable corrosion inhibition efficiency against the corrosion of mild steel in 1 M HCl solution at room temperature. It has been found that Brosadimine shows greater corrosion inhibition efficiency than Sadimine due to extra halogen group presence in the structure. As the concentration of studied inhibitors increases, the corrosion inhibition efficiency of the prepared compounds also increases. This study demonstrated that corrosion inhibitors for metals and alloys can preserve the quality and life of metals from corrosion.